THE RESULTS OF THE PEDAGOGICAL EXPERIMENT IN DEVELOPING SELF-CARE SKILLS TO CHILDREN WITH SEVERE MENTAL RETARDATION OF A SPECIALIZED ORPHANAGE (Education in the 21st Century, 2023)
The article presents the results of the pedagogical educational experiment on the development of self-care skills of children with severe mental retardation of a specialized orphanage.The relevance of the study is attributed to a cause that children with severe mental retardation of a specialized orphanage are constantly under excessive care of nannies, educators and teachers. This leads to the fact that those children are prevented from opportunity to dress / undress themselves, carry out personal hygiene, and serve themselves at the table while eating.177Therefore, it is extremely necessary to research the current problem and to improve the means, strategies and terms for improving the self-care skills of children with severe mental retardation in a specialized orphanage, and to provide an experimental justification for their effectiveness.The present article demonstrates that positive results were obtained based on the selected means, methods and terms for solving this important problem. In the observed areas of activities, the subjects of the study group gained functional self-service skills. The members in the other experimental group had comparatively lower markers.